Assessment of levels of anxiety and fear of Covid-19 in a population of pregnant women in Spain - Muñoz-Vela, Francisco Javier (2023)
Objective: The aim of the study was to assess the levels of fear and anxiety in the particularly vulnerable population group of women during pregnancy.Methods: Cross-sectional study between March 2022 and July 2022 involving 978 pregnant women aged 16 to 50 years. It was carried out based on the scale for the assessment of fear and anxiety in pregnant women (AMICO_Pregnant) and the collection of sociodemographic data. Normality analysis was performed prior to univariate and bivariate statistical analysis.Results: The sample was composed of a total of 978 pregnant women. The mean of the AMICO_Pregnant scale was intermediate (5.04 points; SD=2.36). The bivariate analysis showed a statistically significant relationship between the AMICO_Pregnant scale and the following variables: vaccination schedule status, contact with the disease, weeks of gestation, altered delivery or birth plan.Conclusion: Women with pregnancies closer to term, with no contact with the disease, without a complete vaccination schedule, or who had undergone changes in their delivery or birth plans, showed higher levels of fear and anxiety.